Mergers and acquisitions of transnational corporations: a study of events about the return to the shareholder - Ellwanger, Kim (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The market of mergers and acquisitions in Brazil has been highly active, especially in recent pats years. Given this fact, the present article aims to analyze the stock market reaction to the announcement of such event. To contextualize this business strategy as well as to investigate the reasons that lead companies to adopt such strategy, a literature search was performed. Investment decisions are, according to the Finance Theory, economically attractive when they result in increased share value. One of the possible ways to assess if mergers and acquisitions had benefited the shareholders of companies involved is the reaction given by the capital market at the time of announcement of the transaction. In this article, empirical method called event study was used to analyze the existence of abnormal returns in eighteen Brazilians transnational corporations after announcing the transaction to the stock market. The results, analyzed from a quantitative approach, showed that these operations did not result in significant abnormal returns for investors. However, it should be noted that this does not mean that these processes do not generate value for the company or for the shareholder.